The APLIKASI TEKNOLOGI GRANULATOR PADA KELOMPOK USAHA BERAS ANALOG DI BANDAR SURABAYA LAMPUNG TENGAH - Warji, Warji Warji (Lembaga Penelitian dan Pengabdian Universitas Lampung, 2017)
Cassava have high potency so could increase diversification product from cassava. One of the products is cassava rice (imitation rice). Cassava rice industry have problem about the technology. Produce process still apply conventional technology although cassava rice has been commercial product. Aggregation process is important because influent quality and performance of cassava rice. This program are (1) to applied cassava rice aggregator machine to produce cassava rise, (2) give knowledge about food processing, and (3) to applied packaging. The program was conducted very well, aggregator was applied and accepted partner. The aggregator could operate very well and appropriate with requirement industry partner. After this program, partner knowledge increase 45.2%. Partner hope this program could be continued with applied food processing technology from University of Lampung.